Influencers and Integrity: The Role of Halal Labels and Online Testimonials in Shaping Purchase Intentions for Somethinc Skincare Products - Salim, Anisa Diyanti; Wafa, Faqih El Wafa (Scimadly Publishing, 2025)
This study aims to analyze the influence of celebrity endorsements, online testimonials, and halal labels on the purchasing decisions of Somethinc skincare products among students at UIN Antasari, both partially and simultaneously. The research employs a quantitative approach using a field survey method. The sample was selected through accidental sampling from students who use Somethinc products, and data were collected through questionnaires. Data analysis was conducted using multiple linear regression with the SPSS version 22 application. The F-test results show that simultaneously, the variables of celebrity endorsement, online testimonials, and halal labels have a significant effect on purchasing decisions. However, the t-test results indicate that celebrity endorsement does not have a partial effect, while online testimonials and halal labels have a positive and significant influence on purchasing decisions. Based on these findings, it is recommended that skincare business actors prioritize promotional strategies that emphasize consumer testimonials and the clarity of halal certification as key factors in attracting Muslim consumers, rather than relying solely on celebrity popularity.